2013
DOI: 10.1016/j.jep.2012.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Dentatin isolated from Clausena excavata induces apoptosis in MCF-7 cells through the intrinsic pathway with involvement of NF-κB signalling and G0/G1 cell cycle arrest: A bioassay-guided approach

Abstract: Together, the results demonstrated that the DTN isolated from Clausena excavata inhibited the proliferation of MCF-7 cells, leading to cell cycle arrest and programmed cell death, which was confirmed to occur through the mitochondrial pathway with involvement of the NF-κB signalling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
(30 reference statements)
0
37
0
1
Order By: Relevance
“…The concentration of DEN that causes death of 50% of tested cells or the IC 50 value of DEN was found to be 5.6 µg/mL. Earlier research performed by [7] revealed similar toxicity against Estrogen Receptor positive (ER+) MCF-7 where IC 50 value was at 6.1 µg/mL. In the study mentioned above, DEN exhibited fewer side-effects on the normal cells in comparison to the cancer cells.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…The concentration of DEN that causes death of 50% of tested cells or the IC 50 value of DEN was found to be 5.6 µg/mL. Earlier research performed by [7] revealed similar toxicity against Estrogen Receptor positive (ER+) MCF-7 where IC 50 value was at 6.1 µg/mL. In the study mentioned above, DEN exhibited fewer side-effects on the normal cells in comparison to the cancer cells.…”
Section: Resultsmentioning
confidence: 71%
“…Therefore, exposure time may be prolonged by gradually releasing the DEN from the complex [34]. Moreover, higher resistance was displayed by normal breast MCF10a cells as previously mentioned by [7]. To confirm the selectivity, it can compare the cytotoxicity effects of DEN and DEN-HPβCD complex for cancer cell line with normal cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caspase 8 activation, which is a major participant in extrinsic pathways, is the result of cell death receptors, such as Fas and TNF-α. Activated caspase 8 also leads to the activity of effector caspases, including caspase 3 and caspase 713414243. The treated MDA-MB-231 cells experienced a significant increase in caspase 9 after 24, 48, and 72 hours of treatment.…”
Section: Discussionmentioning
confidence: 98%